Unmet Medical Needs in Chronic, Non-communicable Inflammatory Skin Diseases - Ujiie, Hideyuki; Rosmarin, David; Schön, Michael P.; Ständer, Sonja; Boch, Katharina; Metz, Martin; Maurer, Marcus; Thaci, Diamant; Schmidt, Enno; Cole, Connor; Amber, Kyle T.; Didona, Dario; et al. (Frontiers in Medicine, 2022)
An estimated 20-25% of the population is affected by chronic, non-communicable inflammatory skin diseases. Chronic skin inflammation has many causes. Among the most frequent chronic inflammatory skin diseases are atopic dermatitis, psoriasis, urticaria, lichen planus and hidradenitis suppurativa, driven by a complex interplay of genetics and environmental factors. Autoimmunity is another important cause of chronic skin inflammation. The autoimmune response may be mainly T cell driven, such as in alopecia areata or vitiligo, or B cell driven in chronic spontaneous urticaria, pemphigus and pemphigoid diseases. Rare causes of chronic skin inflammation are autoinflammatory diseases, or rheumatic diseases, such as cutaneous lupus erythematosus or dermatomyositis. Whilst we have seen a significant improvement in diagnosis and treatment, several challenges remain. Especially for rarer causes of chronic skin inflammation, early diagnosis is often missed because of low awareness and lack of diagnostics. Systemic immunosuppression is the treatment of choice for almost all of these diseases. Adverse events due to immunosuppression, insufficient therapeutic responses and relapses remain a challenge. For atopic dermatitis and psoriasis, a broad spectrum of innovative treatments has been developed. However, treatment responses cannot be predicted so far. Hence, development of (bio)markers allowing selection of specific medications for individual patients is needed. Given the encouraging developments during the past years, we envision that many of these challenges in the diagnosis and treatment of chronic inflammatory skin diseases will be thoroughly addressed in the future.